Creating Win-Win Collaborations for Students: An Immersive Learning Project for Advanced Sales Courses - Lastner, Matthew M; Rast, Rebecca; Andzulis, James "Mick" (Journal for advancement of marketing education, 2016)
Purpose of the Study: With the number of university sales programs on the rise, and a growing demand for sales professionals forecast well into the future, a need exists for undergraduate sales course innovations to better prepare the salespeople of tomorrow. Method/Design and Sample: In this paper, we advocate for the design and implementation of immersive learning sales projects that move beyond classroom simulations and mock exercises to provide students with actual real-world selling experience. Results: Through immersive learning, such as the method we propose here, students will enter the sales workforce with a more realistic preview of what will be required for success. Students will also further develop the soft skills essential for a successful career in sales. Value to Marketing Educators: As firms grow more satisfied with the successes of college recruits who have experienced immersive learning, their relationships with sales programs will strengthen, enhancing both sales program recruiting efforts and the potential for donations.